Who should teach rheumatology to medical students, a rheumatologist or an internist? - Towiwat, Patapong; Deoisares, Rawisut; Choomchuay, Nantana; Pannarunothai, Supasit (Naresuan University Journal: Science and Technology (NUJST); Vol 23 No 1 (2015): January-April 2015, 2015)
Introduction : Rheumatology is listed as a special topic in the Thai medical competency assessment criteria of the 2012 national license examination. Lacking of rheumatologist in the affiliate medical centers may affect students’ performances in rheumatology. This study compared medical students’ knowledge scores on rheumatology examination between students taught by a rheumatologist and an internist, and surveyed students’ opinions on teaching of rheumatology by a rheumatologist.         Methods : It was a non-randomized cross-sectional study in 6 medical education centers (MECs). The study was conducted with the sixth-year medical students (n=109). Rheumatologists in 3 MECs directly taught rheumatology to students while in 3 MECs the internists did so.  Sixty multiple choice questions (MCQs) with one best response from 5 choices and a questionnaire, which surveyed students’ opinions on teaching of rheumatology by a rheumatologist.         Results : The knowledge scores from the 60 MCQs revealed that students in the rheumatologist teaching group had slightly higher but not significantly different total scores than students in the internist teaching group (31.74±5.47 vs. 30.49±7.37, p value 0.32). The scores from “must know” items were also not significantly different between the two groups (20.57±4.27 vs. 20.42±5.92, p value 0.88). However, the scores on “should know” items of students from the rheumatologist teaching group had significantly higher scores than the internist teaching group (11.18±2.15 vs. 10.06±2.60, p value 0.03. Most medical students expressed the need to learn rheumatology from a rheumatologist with the expectation that a rheumatologist provides more emphasis on clinical and practical points than the internist does.         Conclusions : In the 3 MECs where the sixth-year medical students were taught by rheumatologists, a significant difference was found in “should know” knowledge of rheumatology but the “must know” and total scores were not significantly different.  Most sixth-year medical students believed that teaching by rheumatologists would help them focus on clinical and practical points more than teaching by general internal medicine staff. Keywords : Musculoskeletal, Undergraduate, Rheumatologist, Internist
Keywords: Musculoskeletal, Undergraduate, Rheumatologist, Internist